Internet-based videoconferencing and data collaboration for the imaging community - Poon, David P.; Langkals, John W.; Giesel, Frederik L.; Knopp, Michael V.; Tengg-Kobligk, Hendrik von (Journal of computer assisted tomography, 2011)
Internet protocol-based digital data collaboration with videoconferencing is not yet well utilized in the imaging community. Videoconferencing, combined with proven low-cost solutions, can provide reliable functionality and speed, which will improve rapid, time-saving, and cost-effective communications, within large multifacility institutions or globally with the unlimited reach of the Internet. The aim of this project was to demonstrate the implementation of a low-cost hardware and software setup that facilitates global data collaboration using WebEx and GoToMeeting Internet protocol-based videoconferencing software. Both products’ features were tested and evaluated for feasibility across 2 different Internet networks, including a video quality and recording assessment. Cross-compatibility with an Apple OS is also noted in the evaluations. Departmental experiences with WebEx pertaining to clinical trials are also described. Real-time remote presentation of dynamic data was generally consistent across platforms. A reliable and inexpensive hardware and software setup for complete Internet-based data collaboration/videoconferencing can be achieved.
Gesehen am 05.01.2023